Rotation of intramedullary alignment rods affects distal femoral cutting plane in total knee arthroplasty. - Maderbacher, Günther; Matussek, Jan; Keshmiri, Armin; Greimel, Felix; Baier, Clemens; Grifka, Joachim; Maderbacher, Hermann (Knee Surgery, Sports Traumatology, Arthroscopy, 2018)
Purpose: Intramedullary rods are widely used to align the distal femoral cut in total knee arthroplasty. We hypothesised that both coronal (varus/valgus) and sagittal (extension/flexion) cutting plane are affected by rotational changes of intramedullary femoral alignment guides.Methods: Distal femoral cuts using intramedullary alignment rods were simulated by means of a computer-aided engineering software in 4°, 6°, 8°, 10°, and 12° of valgus in relation to the femoral anatomical axis and 4° extension, neutral, as well as 4°, 8°, and 12° of flexion in relation to the femoral mechanical axis. This reflects the different angles between anatomical and mechanical axis in coronal and sagittal planes. To assess the influence of rotation of the alignment guide on the effective distal femoral cutting plane, all combinations were simulated with the rod gradually aligned from 40° of external to 40° of internal rotation.Results: Rotational changes of the distal femoral alignment guides affect both the coronal and sagittal cutting planes. When alignment rods are intruded neutrally with regards to sagittal alignment, external rotation causes flexion, while internal rotation causes extension of the sagittal cutting plane. Simultaneously the coronal effect (valgus) decreases resulting in an increased varus of the cutting plane. However, when alignment rods are intruded in extension or flexion partly contradictory effects are observed. Generally the effect increases with the degree of valgus preset, rotation and flexion.Conclusion: As incorrect rotation of intramedullary alignment guides for distal femoral cuts causes significant cutting errors, exact rotational alignment is crucial. Coronal cutting errors in the distal femoral plane might result in overall leg malalignment, asymmetric extension gaps and subsequent sagittal cutting errors.